Effect of Packaging Material Types on Antioxidant Activity, Fat Content, and Ash Content in the Imported and Local Yellow Soybean Tempeh - Diah Ayu Puspasari; Zaki Utama; Andriati Ningrum (The University of Lampung, 2023)
Tempeh known as indigenous food that has high nutrients and antioxidant compounds. Tempeh was produced from the fermentation of soybean with Rhizopus sp. Tempeh usually was wrapped with plastic or banana leaf. The purpose of this study to know the effect of soybean originated (import and local soybean) and the packaging material types (plastic, teakwood leaf, hibiscus leaf, and banana leaf) on antioxidant activity, fat content, and ash content of tempeh. The methods of this research were antioxidant activity analyses with DPPH (1,1-diphenyl-2- picrylhydrazil) Radical Scavenging Activity method, fat analyses with soxhlet method, ash analyses with dry method. The results of this research showed that the tempeh from local soybeans with waru leaf packaging had the highest antioxidant activity (53,43%), tempeh from import soybeans with plastic packaging had the highest fat content (48,89%), and tempeh from import soybeans with waru leaf packaging had the highest ash content (2,19%). We found that the soybean origin (import and local soybean) and the packaging types (plastic, waru leaf, jati leaf, and banana leaf) had significant effect (p<0,05) on antioxidant activity, fat content, and ash content of tempeh. Keywords: Antioxidant activity, Ash content, Fat content, Soybean, Tempeh.